Eroticism and Justice: Harold Pinter’s Screenplay of Ian McEwan’s The Comfort of Strangers - Mirowska, Paulina (Text Matters: A Journal of Literature, Theory and Culture, 2013)
A careful analysis of Harold Pinter’s screenplays, notably those written in the 1980s and early 1990s, renders an illustration of how the artist’s cinematic projects supplemented, and often heightened, the focus of his dramatic output, his resolute exploration of the workings of power, love and destruction at various levels of social interaction and bold revision of received values. It seems, however, that few of the scripts did so in such a subtle yet effective manner as Pinter’s intriguing fusion of the erotic, violence and ethical concerns in the film The Comfort of Strangers (1990), directed by Paul Schrader and based on Ian McEwan’s 1981 novel of the same name. The article centres upon Pinter’s creative adaptation of McEwan’s deeply allusive and disquieting text probing, amongst others, the intricacies and tensions of gender relations and sexual intimacy. It examines the screenplay—regarded by many critics as not merely an adaptation of the novel but another, very powerful work of art—addressing Pinter’s method as an adapter and highlighting the artist’s imaginative attempts at fostering a better appreciation of the connections between authoritarian impulses, love and justice. Similarly to a number of other Pinter filmscripts and plays of the 1980s and 1990s, the erotic and the lethal alarmingly intersect in this screenplay where the ostensibly innocent—an unmarried English couple on a holiday in Venice, who are manipulated, victimized and, ultimately, destroyed—are subtly depicted as partly complicit in their own fates.